Harmful Lepidoptera in Czechia - current status, changes and importance - Šefrová, Hana; Laštůvka, Zdeněk (Mendelova univerzita v Brně, 2023)
An analysis of the current harmfulness of moths and butterflies (Lepidoptera) in Czechia was carried out. In total, about 50 species (1.4% of the Czech fauna) of regular or at least occasional pests with a not insignificant economic importance are registered. Of these, 16 (30%) damage field and garden crops, 15 (28%) fruit trees and grapevine, 7 (13%) ornamental greenery, 6 (12%) forest trees and 9 (17%) stored materials. The causes of possible changes in species composition and pest abundance are briefly discussed. The species spectrum of pests has clearly narrowed over the last decades. The loss of harmfulness has usually occurred in less significant, but also in some formerly important pests. The increase of new pests is minimal. In the last 30 years, two newly introduced harmful non-native (invasive) species (Cameraria ohridella and Cydalima perspectalis) were recorded (4 since the mid-20th century). No new Lepidoptera pests have been registered during this period, which have spread spontaneously into Czechia, e.g. due to climate change. About 50 species of moths and butterflies can currently be considered pests of plants or stored materials in Czechia (1.4% of all species). The species spectrum of pests has been narrowing over time, with minor pests losing their importance, as well as some formerly important pests. The importance of most important pests remains more or less the same in the long term, with varying degrees of fluctuation. In the past 30 years, 2 new (introduced) non-native pest species have been registered in Czechia and 2 more are being introduced repeatedly to greenhouses.
Keywords: Lepidoptera; pests; agriculture; silviculture; ornamental greenery; stored materials